2010
DOI: 10.1136/jnnp.2009.204008
|View full text |Cite
|
Sign up to set email alerts
|

The ADAS-cog in Alzheimer's disease clinical trials: psychometric evaluation of the sum and its parts

Abstract: Performance was satisfactory at the scale level, but most ADAS-cog components were too easy for many patients in this sample and did not reflect the expected depth and range of cognitive performance. The clinical implication of this finding is that the ADAS-cog's estimate of cognitive ability, and its potential ability to detect differences in cognitive performance under treatment, could be improved. However, because of the limitations of traditional psychometric methods, further evaluations would be desirable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
123
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(131 citation statements)
references
References 34 publications
8
123
0
Order By: Relevance
“…For longitudinal studies, 20 additional patients with AD were identified retrospectively based on their provision of blood twice at the Mayo Clinic or the University of Kentucky, first when cognitively intact and later at diagnosis of AD (table 1). Intervals between the 2 blood samples (number of patients) were 1 to 5 years (7) and 6 to 10 years (13). Each patient in both cross-sectional and longitudinal groups had mental status testing and an MRI, and some had measurements of CSF Ab1-42, total tau, and P-T181-tau.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For longitudinal studies, 20 additional patients with AD were identified retrospectively based on their provision of blood twice at the Mayo Clinic or the University of Kentucky, first when cognitively intact and later at diagnosis of AD (table 1). Intervals between the 2 blood samples (number of patients) were 1 to 5 years (7) and 6 to 10 years (13). Each patient in both cross-sectional and longitudinal groups had mental status testing and an MRI, and some had measurements of CSF Ab1-42, total tau, and P-T181-tau.…”
mentioning
confidence: 99%
“…7,8 Those with probable AD and mild to moderate dementia were diagnosed by Dubois criteria 11 Mini-Mental State Examination (MMSE) and the Alzheimer's Disease Assessment Scale-cognitive subscale were conducted as described. 12,13 Twenty-four of the 26 cross-sectional patients with AD were taking an acetyl-cholinesterase inhibitor and/or memantine, and 5 were on antidepressant medications.…”
mentioning
confidence: 99%
“…Scaling assumptions determine whether summing subscales of the instrument to create a single scale score is appropriate. Targeting evaluates whether the range of cognitive performance measured by the battery corresponds to the range of the sample (Cano et al, 2010). Effect size correlations can provide convenient and informative indices of construct validity (Westen, & Rosenthal, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Cano et al 13 evaluated the psychometric properties of both the individual components of the ADAS-Cog and the total score. Convergent validity with respect to Mini Mental Status Exam scores was satisfactory (0.63) and ADAS-Cog scores were not affected by age or gender.…”
Section: Short Communicationmentioning
confidence: 99%